Continuous monitoring and continuous auditing implementation in Indonesian Higher Education - Yusar Sagara; Faisal Akbar (Jurnal Akuntansi dan Auditing Indonesia, 2021)
Indonesian higher education needs to operate its activity based on productivity and efficiency. However, in reality, it faces several issues, including but not limited to lack of standard of operation, financial fraud, and non-compliance with applicable regulations. Continuous Monitoring (CM) and Continuous Auditing (CA) are essential to prevent issues related to the institution's circumstances. This research explains how organizational culture, information quality, and intellectual capital affect CM and CA applications. This study obtained the data through questionnaires sent to 102 members of the internal control unit. Using the Partial Least Square-Structural Equation Modeling to analyze the data. The results showed a positive and significant influence of organizational culture on the applications of CM and CA. Other findings are that information quality and intellectual capital had a positive and significant influence on CA application. On the other hand, information quality and intellectual capital have a positive but insignificant influence on CM application.